Pengaruh Media Sosial Dan Status Sosial Ekonomi Orang Tua Terhadap Perilaku Konsumtif Mahasiswa Program Studi Pendidikan Ekonomi Universitas Hamzanwadi - Susilawati Susilawati; Muhammad Zainul Majdi; Julian Hesty Rahayu; Rohaeniah Zain (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This study aims to determine the positive and significant influence of social media and the socioeconomic status of parents on the consumptive behavior of students in the Economics education program at Hamzanwadi University partially. This research is a research using descriptive analysis method with a quantitative approach. Data collection techniques in this study using questionnaires and documentation. The population in this study were students of the Hamzanwadi University Economics education study program, totaling 385 students with a research sample of 79 students who were taken by simple random sampling. The method of data analysis using the Partial Least Square (PLS) Model Scheme, Outer Model Evaluation, and Evaluation Of Structural Model, as well as. The results of the study show that: (1) Social media does not have a positive influence on consumptive behavior on the consumptive behavior of students of the Economic Education Study Program at Hamzanwadi University of 0.018, because the T statistic value is 1.277 which means it is smaller than 1.96, so the hypothesis Ha1 can be stated not accepted. (2) Social status has a positive influence on consumptive behavior on the consumptive behavior of students of the Hamzanwadi University Economics Education Study Program of 0.540, because the T statistic value is 6.655 which means it is greater than 1.96, so Ha2 can be declared accepted.